The Impact of Content Marketing in an E-Commerce Live Shopping Program on Consumer’s Purchasing Decision (Research on Tokopedia Play’s In-House Live Shopping Program: Night Deals) - Fathma, Mutiara Annisa; Kartikawangi, Dorien (Indonesia Marketing Association (IMA), 2024)
The rise of technology advancement has led to many aspects of life becoming digitized. One of the aspects of life that has been digitized and also reformed through innovation is shopping in the form of Live shopping. Various e-commerce such as Tokopedia, is now utilizing this as their content marketing strategy to gain more attraction and purchase from its users. This study would like to research on the impact of Tokopedia Play Night Deal’s Content Marketing towards a consumer’s purchasing decision. Based on content marketing and purchasing decision theories, this research use quantitative approach. The independent variable in this study is content marketing and the dependent variable is purchasing decision. This study utilizes 102 samples from the greater Jakarta area (JABODETABEK). This research utilizes a simple linear regression analysis. The result of this research is that content marketing has a significant impact towards a consumer’s purchasing decision.